Near-fiber electromyography. Issue 5 (May 2021) - Piasecki, Mathew; Garnés-Camarena, Oscar; Stashuk, Daniel W.
Highlights: Near fiber EMG (NFEMG) focuses on contributions from individual or small groups of near motor unit fibers to detected near fiber motor unit potentials (MUPs). Near fiber MUP duration and dispersion increases can indicate early and progressive axonal sprouting with conduction slowing or neuromuscular junction transmission delay and/or increased MU fiber diameter variability. Increases in near fiber MUP jiggle and segment jitter can indicate early and progressive increases in electrophysiological temporal variability for the near fibres (i.e. NF jitter). Abstract: Objective: Describe and evaluate the concepts of near fiber electromyography (NFEMG), the features used, including near fiber motor unit potential (NFMUP) duration and dispersion, which relate to motor unit distal axonal branch and muscle fiber conduction time dispersion, and NFMUP segment jitter, a new measure of the temporal variability of neuromuscular junction transmission (NMJ), and axonal branch and muscle fibre conduction for the near fibres (i.e. NF jitter), and the methods for obtaining their values. Methods: Trains of high-pass filtered motor unit potentials (MUPs) (i.e. NFMUP trains) were extracted from needle-detected EMG signals to assess changes in motor unit (MU) morphology and electrophysiology caused by neuromuscular disorders or ageing. Evaluations using simulated needle-detected EMG data were completed and example human data are presented. Results: NFEMG feature values can be used to detect axonal sprouting, conduction slowing and NMJ transmission delay as well as changes in MU fiber diameter variability, and NF jitter. These changes can be detected prior to alterations of MU size or numbers. Conclusions: The evaluations clearly demonstrate and the example data support that NFMUP duration and dispersion reflect MU distal axonal branching, conduction slowing and NMJ transmission delay and/or MU fiber diameter variability and that NFMUP jiggle and segment jitter reflect NF jitter. Significance: NFEMG can detect early changes in MU morphology and/or electrophysiology and has the potential to augment clinical diagnosis and tracking of neuromuscular disorders.